Adsorptive removal of arsenic from drinking water using KOH-modified sewage sludge-derived biochar - Ahsan Shah; Arun Arjunan; Anusha Thumma; Julia Zakharova; Timothy Bolarinwa; Shreah Devi; Maryam Batool (Cleaner Water)
This paper reveals a green chemistry approach to remove arsenic (As+3) from water using potassium hydroxide (KOH) modified sewage sludge-derived biochar (SSDB-KOH). Characterisation of the morphology, particle size and composition of the SSDB-KOH pre- and post-adsorption confirmed porous and heterogenous surface favouring adsorption. At ambient temperature (20 °C), the SSDB-KOH dose of 20 g/l achieved 98 % arsenite removal at nearly neutral solution pH (8). This compared favourably with pristine SSDB, where the performance was limited to 41.6 % removal. The enhanced arsenite adsorption of SSDB-KOH was informed by several mechanisms, including ionic interactions, pore filling and metal-pi interactions. The experimental data fits closely with the Langmuir isotherm and pseudo-second-order kinetic models, revealing monolayer adsorption and the chemical interaction between adsorbents and the adsorbate. The spontaneous and endothermic nature of the process was confirmed by the negative value of ΔG and the positive value of ΔH, respectively. The performance of the biochar was evaluated for four-cycle regeneration. Finally, a cost analysis was performed to demonstrate the economic feasibility of using SSDB-KOH to remove arsenic from water.